2011
DOI: 10.1212/wnl.0b013e31822cfc2f
|View full text |Cite
|
Sign up to set email alerts
|

Loss of network efficiency associated with cognitive decline in chronic epilepsy

Abstract: These findings support the hypothesis that chronic localization-related epilepsy causes cognitive deficits by inducing global cerebral network changes instead of a localized disruption only. Whether this is the result of epilepsy per se or the use of antiepileptic drugs remains to be elucidated. For application in clinical practice, future studies should address the relevance of altered cerebral network topology in prediction of cognitive deficits and monitoring of therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
135
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 36 publications
18
135
2
2
Order By: Relevance
“…Next, the individual anatomical T1 segmentations were registered to the fMRI images (24) to calculate the average time series for the cortical and subcortical gray and white matter areas and CSF. To reduce the effect of physiological noise (respiratory and cardiac artifacts), the fMRI data were filtered by using a band pass filter (0.01-0.1 Hz) and linear regression with the averaged time series of white matter, CSF, and movement parameters acquired in the previous realignment step as nuisance regressors (25,26). Finally, the averaged time series of the cortical and subcortical segmented areas (27,28) (a total of 82 areas, 41 for each hemisphere) was used to form a correlation matrix by calculating the Pearson correlation coefficients between all pairs of the segmented brain areas.…”
Section: Image Preprocessingmentioning
confidence: 99%
“…Next, the individual anatomical T1 segmentations were registered to the fMRI images (24) to calculate the average time series for the cortical and subcortical gray and white matter areas and CSF. To reduce the effect of physiological noise (respiratory and cardiac artifacts), the fMRI data were filtered by using a band pass filter (0.01-0.1 Hz) and linear regression with the averaged time series of white matter, CSF, and movement parameters acquired in the previous realignment step as nuisance regressors (25,26). Finally, the averaged time series of the cortical and subcortical segmented areas (27,28) (a total of 82 areas, 41 for each hemisphere) was used to form a correlation matrix by calculating the Pearson correlation coefficients between all pairs of the segmented brain areas.…”
Section: Image Preprocessingmentioning
confidence: 99%
“…Previous studies have examined brain efficiency in both functional networks (Vlooswijk et al, 2011;Wang et al, 2014;Zhang et al, 2011) and structural networks in epilepsy (Bernhardt et al, 2011;Liu et al, 2014). However, these findings have remained conflicting potentially due to various factors such as different data processing approach and heterogeneous study population.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported differences in clustering, path length, and efficiency from a range of diseases and disorders including Alzheimer's disease (Lo et al, 2010;SanzArigita et al, 2010;Yao et al, 2010), multiple sclerosis (He et al, 2009b;Shu et al, 2011), depression (Zhang et al, 2011a), obsessive compulsive disorder (Zhang et al, 2011b), and synesthesia (Hä nggi et al, 2011). In two separate studies on epilepsy, one group reported lower path length between patients with epilepsy and the control group (Liao et al, 2010); whereas another study showed an increase (Vlooswijk et al, 2011). Further inquiry to determine the direction of global changes in the network neglects the bigger question: Does the direction of change imply that the network has entered a particular disease state?…”
Section: Discussionmentioning
confidence: 99%